(untitled) (The Pakistan Development Review, 1989)
Throughout the remarkable growth of institutional rural credit in Pakistan there has been an underlying concern for its provision to the small farmers and those unable to compete in the market for reasons of inadequate collateral or repayment capacity. It is felt that the provision of credit for production purposes would enable the small farmers to avail of the benefits of the seed-fertilizer revolution and equip them in time with the repayment capacity required to qualify for loans in the open market. With this end in view the government continued, and continues to, heavily subsidize the provision of agricultural credit in Pakistan. According to official statistics, in 1984-85 about 89 percent of the total credit disbursed in Pakistan by the Federal Bank for Cooperatives went to the small farmers (those owning 12.5 acres or less); 70 percent of ADBP loan recipients and 90 percent of commercial bank loan recipients owned less than 25 acres of land [see Government of Pakistan (1985)]. However, a number of independent studies contradict these official figures [see for example National Fertilizer Corporation (1984) and Punjab Economic Research Institute (1986 and 1986a)]. This paper looks at the changing relative importance of institutional sources of credit in Pakistan and presents evidence on the limited access of the small farm households to these subsidized sources of credit. Some evidence is also presented 011 the significantly higher rates of interest that borrowers have to pay on loans from non-institutional sources than they have to pay for similar loans from institutional sources for different purposes of utilization.